2006
DOI: 10.1111/j.1439-0531.2006.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicle Ablation Improves the Ovarian Response and the Number of Collected Embryos in Superovulated Cows During the Early Stages of Lactation

Abstract: A field study was designed to compare ovarian response and embryo yield in cows during early lactation when gonadotropin administration followed one of four treatments. In group 1A (n = 19) and 1B (n = 9), the estrouses were synchronized by two prostaglandin F2alpha (PG) injections given 11 days apart, and starting from day 9 of the synchronized cycle superovulation was conducted with eight decreasing dose of FSH. In group 1B, ablation of all follicles >3 mm was carried out on day 8. In group 2A and 2B (each n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
0
3
0
3
Order By: Relevance
“…Merton et al., showed that dominant follicle ablation increased the number of ovulations and viable embryos, especially in cows (Merton et al. 2003; Amiridis et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Merton et al., showed that dominant follicle ablation increased the number of ovulations and viable embryos, especially in cows (Merton et al. 2003; Amiridis et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Particularmente, hembras bovinas de origen Bos indicus presentan elevados concentraciones circulantes de factor de crecimiento similar a insulina (IGF) en comparación a animales Bos Taurus, esta característica ha sido relacionada con una población folicular elevada propia de hembras de esta subespecie (21), por consiguiente, al trabajar con vacas de la raza Brahman, una considerable cantidad de folículos se encuentran disponibles y con posibilidad de responder adecuadamente a los tratamientos de SPO (13,22) Al comparar las dos metodologías, fue observado que el uso de la ablación folicular aumentó el porcentaje de embriones de calidad 1. Ha sido ampliamente demostrado que la ausencia de un folículo dominante al inicio de la estimulación del crecimiento folicular con FSH exógena, es uno los factores que mayor influencia tienen en la respuesta superovulatoria, no solamente en lo referente al número de ovulaciones, sino además en la calidad de las estructuras recuperadas (4,23).…”
Section: Resultsunclassified
“…Empirical evidence suggested that elimination of the dominant follicle prior to superovulation induced a new follicular wave emergence which improved the ovarian response to gonadotrophic stimulation [3,4,[13][14][15]. However, D1 protocol had the same merit of absence of the dominant follicle (D.F) after spontaneous ovulation however; the number of emerged follicles was significantly lower than the no-CL protocol.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the initiation of the FSH treatment at the time of wave emergence elicited a high superovulation response [2]. Furthermore, removal of the dominant follicle by ablation [3,4] or injection of GnRH [5] increased the number of recruited follicles and synchronized the follicular wave emergence [4]. Some researchers have focused on starting the superovulation protocol at the first wave in which the wave emergence occurred at a consistent point (after ovulation) and in the absence of dominant follicle.…”
Section: Introductionmentioning
confidence: 99%